2011
DOI: 10.1186/1756-8935-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin regulated interchange between polycomb repressive complex 2 (PRC2)-Ezh2 and PRC2-Ezh1 complexes controls myogenin activation in skeletal muscle cells

Abstract: BackgroundPolycomb group (PcG) genes code for chromatin multiprotein complexes that are responsible for maintaining gene silencing of transcriptional programs during differentiation and in adult tissues. Despite the large amount of information on PcG function during development and cell identity homeostasis, little is known regarding the dynamics of PcG complexes and their role during terminal differentiation.ResultsWe show that two distinct polycomb repressive complex (PRC)2 complexes contribute to skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 46 publications
6
121
0
Order By: Relevance
“…Alternatively, an additional contribution to the H3K27me3 enrichment at the Runx2 promoter by a PRC2 complex carrying EZH1 as the catalytic subunit needs to be considered. It has been shown that during myoblast differentiation nuclear PRC2-EZH1 concentrations are drastically increased (55), where this complex is found to mediate important regulatory functions. Remarkably, the increased in H3K27me3 enrichment at the Runx2 P1 promoter during myoblast differentiation occurs in the presence of the H3K27me3 demethylase UTX.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, an additional contribution to the H3K27me3 enrichment at the Runx2 promoter by a PRC2 complex carrying EZH1 as the catalytic subunit needs to be considered. It has been shown that during myoblast differentiation nuclear PRC2-EZH1 concentrations are drastically increased (55), where this complex is found to mediate important regulatory functions. Remarkably, the increased in H3K27me3 enrichment at the Runx2 P1 promoter during myoblast differentiation occurs in the presence of the H3K27me3 demethylase UTX.…”
Section: Discussionmentioning
confidence: 99%
“…39 Surprisingly, during muscle differentiation, several evidences showed a role of EZH1 in transcriptional activation. 40,41 PRC1 and PRC2 are able to induce gene silencing independently by each other, 42,43 or by a more common synergistic mechanism. Establishment of H3K27me3 by PRC2 complex induces the recruitment of PRC1.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ezh2-mediated H3K27me3 marks are specifically present on genes associated with alternative lineage selection, although Ezh2 dos not suppress terminal differentiation into skeletal muscle [80] . In contrast to PRC2-Ezh2, PRC2-Ezh1 is required for the myogenic differentiation of SCs; specifically, PRC2-Ezh1 replaces PRC2-Ezh2 on the myogenin promoter to regulate the appropriate timing of the transcriptional activation of myogenin [81] . When SCs differentiate, HDAC1 downregulation and pRb hypo-phosphorylation occurs, enabling the formation of the pRb-HDAC1 complex in differentiated myotubes.…”
Section: Epigenetic Control Of Sc Differentiationmentioning
confidence: 99%